Socialization of the Importance of Parenting in Forming Children's Character in Jayamulya Village, Kroya District, Indramayu Regency - Dian Zahra N.; Hasanudin; Dini Nurfajri H.; Tasiroh (Aimmah: Social Sciences Journal, 2025)
The importance of parents knowing good parenting for the development and growth of a child, especially in the formation of early childhood character. Because in the formation of a child's character, the first person who provides character education for their child is the parent. With the development of the times, the parenting pattern of parents towards children has decreased and decreased, most parents are busy with work so that they cannot accompany the growth and development of their children optimally. In addition, many parents do not understand about parenting, how to raise children well, which is in accordance with religious values and socio-moral values of life, most parents see that children, after entering adolescence, are considered capable of managing and taking care of their own lives so that many children have bad relationships due to lack of parental control in the growth and development of children and character education of children. Based on these problems, a work program on Good Parenting was planned which was held in the Jayamulya Village Hall. The purpose of implementing the program is to provide information and further direction for the Community and parents on how to educate children based on character education with and efforts to implement character education programs for children. Provide insight into great parents with character. Activities are carried out using the caramah method and discussion. In the implementation of this activity, it was delivered through a Seminar, where the implementation brought in experienced speakers who had broad insights related to character education. The target in the work program is the Family Empowerment and Welfare (PKK) group. This study uses a qualitative method because this study intends to provide information about the importance of Parenting. The expected output target from the work program that will be carried out is that the community or parents can feel the presence and benefits of these programs. As well as good changes from the community, especially parents who have children to become better after activity.